Fundamentals of Electric Drives, 2nd Edition - Mohamed El-Sharkawi (Cengage Learning, 2018)
Master the basic topics and fundamental concepts underlying electric machines, power electronics, and electric drives with FUNDAMENTALS OF ELECTRIC DRIVES, 2nd Edition. While other books on electric drives concentrate on converters and waveform analysis and ignore mechanical load dynamics or emphasize motor characteristics with little analysis of converters and controllers, this unique approach provides a complete overview of the subject at a level that's ideal for full comprehension. Readers follow the analysis and design of a complete electric drive system with coverage of mechanical loads, motors, converters, sensing, and controllers. The author clearly presents drive applications to electric traction, robotics, and wind energy throughout the book. With its practical content, this book serves as a useful reference for both professional and aspiring electric drive engineers. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.